Coxiella burnetii in ruminants from Somalia - Aamir M. Osman; Ahmed A. Hassan-Kadle; Igor S. Silito; Caroline Tostes Secato; Abdalla M. Ibrahim; Maria Carolina A. Serpa; Marcos R. André; Thállitha S. W. J. Vieira; Marcelo B. Labruna; Rosangela Z. Machado; Rafael F. C. Vieira (Tropical Animal Health and Production, 2025)
Q fever in humans and coxiellosis in ruminants are caused by Coxiella burnetii , a zoonotic obligate intracellular bacterium. This infection poses significant health and economic risk. Effective control strategies rely on a thorough understanding of their epidemiology. In this study, we examined the prevalence of C. burnetii in 372 ruminants (190 goats, 133 cattle, and 49 sheep) from the Lower Shabelle and Benadir Regions of Somalia. Diagnostic testing was performed using a quantitative PCR (qPCR) assay that targets the bacterium’s repetitive element IS111 and the Indirect Fluorescent Antibody Test (IFAT) against the C. burnetii strain At12. A total of 47 out of 372 (12.6%) ruminants tested positive for anti- Coxiella burnetii IgG antibodies, with seropositivity detected in 40 out of 190 goats (21.1%) with endpoint titers ranging from 64 to 2,048, and 7 out of 49 sheep (14.3%) with endpoint titers ranging from 64 to 8,192, while all cattle tested negative. Notably, only one goat that was seropositive also tested positive for C. burnetii by qPCR, while all other ruminants were negative. These findings provide evidence of the presence of C. burnetii in Somali livestock, emphasizing its public health risk and highlighting the necessity for targeted surveillance and control strategies to prevent zoonotic transmission.